Association Between Quality Of Sleep With Primary Headache In Siloam Hospital Karawaci - Andriani, Christin; Gunawan, Pricilla Yani (Fakultas Kedokteran Universitas Pelita Harapan, 2021)
A primary headache is the most common neurological complaint and is experienced by almost everyone throughout life. The most common type of primary headache is TTH (Tension-Type Headache) and Migraine. Quality of sleep is associated with life satisfaction and data shows that one-third of adults are affected by poor sleep. Many studies have mentioned that there is a relationship between quality of sleep and primary headache, but no study has ever been conducted in Siloam Hospital Karawaci. We did a case-control study in Siloam Hospital Karawaci using purposive sampling, with a total of 50 patients as the subjects. Data were collected using the PSQI questionnaire and DASS 42 between January 2019 - March 2019. It was found that there was a significant relationship between sleep quality and primary headache (p= <0,001).